PENGARUH PENGELOLAAN SUMBER DAYA MANUSIA, KOMUNIKASI INTERPERSONAL DAN MOTIVASI KERJA YANG BERDAMPAK PADA KINERJA KOPERASI SETIA BUDI WANITA MALANG - Bambang Sigit; Choirul Insyiah (Universitas 17 Agustus 1945 Surabaya, 2023)
This study was conducted to analyze and reveal the influence of human resource management and interpersonal communication on work motivation, which in turn affects the performance of cooperatives. The research design employed in this study is qualitative, and the data were collected through questionnaires and interviews from 75 respondents who are members and administrators of cooperatives. The results of this study demonstrate that human resource management and interpersonal communication have a significant influence on the work motivation of administrators and members in cooperative settings. Additionally, work motivation significantly affects the performance of cooperatives. This implies that interpersonal communication and motivation are key factors in successfully improving the performance of cooperatives, particularly in relation to the implementation of human resource governance, communication, and work motivation among cooperative administrators and members.